2012
DOI: 10.3892/ijmm.2012.948
|View full text |Cite
|
Sign up to set email alerts
|

Μolecular impact of bone morphogenetic protein�7, on lung cancer cells and its clinical significance

Abstract: Abstract. The aim of this study was to investigate the expression of bone morphogenetic protein 7 (BMP7), in human pulmonary cancer tissues/cells and to evaluate the cellular impact of bone morphogenetic proteins on pulmonary cancer cells. BMP7 expression was determined in human lung cancer cell lines. The invasiveness and growth of cells transfected with BMP7, in vitro, were evaluated using the in vitro invasion assay and in vitro tumour models. Cellular migration was analysed using wounding assays. BMP7-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Moreover, shRNA-mediated Bmp7 gene silencing reduced the viability of rat primary PCC cells, suggesting that in this experimental system Bmp7 sustains cell survival. Thus, similar to what has been reported for lung cancer [ 41 ], melanoma [ 42 ] and, albeit controversial, for breast cancer [ 25 ], BMP7 exerts a tumor-promoting action in PCC.…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, shRNA-mediated Bmp7 gene silencing reduced the viability of rat primary PCC cells, suggesting that in this experimental system Bmp7 sustains cell survival. Thus, similar to what has been reported for lung cancer [ 41 ], melanoma [ 42 ] and, albeit controversial, for breast cancer [ 25 ], BMP7 exerts a tumor-promoting action in PCC.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with our findings in chondrosarcoma cells. Clinical reports have also indicated that a high-expression level of BMP-7 may serve as a biomarker for metastasis and poor prognosis in various malignancies, such as esophageal cancer [38], lung cancer [18], gastric cancer [3], colorectal cancer [15], liver cancer [39], and melanoma [5].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence reveals that high-level expression of BMP-7 correlates with increased invasion and metastasis in various malignancies, including breast cancer [14], colorectal cancer [15], prostate cancer [16], esophageal cancer [17], gastric cancer [3], lung cancer [18], liver cancer [6], and melanoma [5]. Although the roles of BMP-7 have emerged as an important factor in the regulation of cell motility across diverse cancer, the influence of BMP-7 on the motility of chondrosarcoma cells still remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…BMP7 has been reported in a wide range of human cancers and is associated with metastasis and poor prognosis 8 – 13 . In lung cancer, BMP7 overexpression was associated with lymph node involvement and an indicator of bone metastasis 14 , 15 . The immune-regulatory functions of BMPs are not well understood.…”
Section: Introductionmentioning
confidence: 99%